Anterior segment surgery early after corneal wound repair. Issue 12 (December 1977) - Maul, E; Muga, R
Abstract : Penetrating wounds of the cornea require immediate repair, generally within 24 hours. Tight closure of the wound and a reformed anterior chamber are the primary goals of surgery. However, there is no guarantee that further surgery will not be required for maintaining the healthy function of the anterior segment. At the second operation the effect of the procedure on the previously repaired wound is of prime importance, since in many cases the operation needs to be done before corneal healing is completed. In our series the lens, which was either partially or completely cataractous at the initial operation, became intumescent at different times afterwards, and an immediate removal was necessary. No change in the preoperative wound sealing or transparency of the cornea could be detected after lens surgery performed between 24 hours and 21 days from the initial corneal repair.